Preoperative Physiology, Imaging, and Management of Transposition of the Great Arteries. (September 2015) - Files, Matthew D.; Arya, Bhawna
Transposition of the great arteries (TGA) refers to hearts with concordant atrioventricular connections but discordant ventriculoarterial connections. In this lesion, the aorta arises from the right ventricle and the pulmonary artery arises from the left ventricle. As such, the pulmonary and aortic circulations run in parallel as opposed to in series, and this lesion is not compatible with survival without adequate mixing of these circulations. The management and outcomes of TGA parallels the field of pediatric cardiac surgery itself. Uniformly fatal in childhood, palliative procedures from the 1950s to 1970s offered survival, albeit at a high early and late cost. In the 1970s, the arterial switch operation (ASO) provided an anatomical "cure, " with survival to adulthood in the current era of around 90%. Detailed perioperative imaging, attention to associated lesions, and comprehension of the physiology are critical to medical and surgical management.